2014
DOI: 10.1179/1607845414y.0000000220
|View full text |Cite
|
Sign up to set email alerts
|

G-CSF induces up-regulation of CXCR4 expression in human hematopoietic stem cells by beta-adrenergic agonist

Abstract: Introduction C-X-C chemokine receptor type 4/stromal-derived factor-1 (CXCR4/SDF-1) axis dynamically mediates hematopoietic stem cell trafficking in the bone marrow (BM). Granulocyte colony-stimulating factor (G-CSF) as the most effective mobilizing agent induces SDF-1 secretion from BM stromal cells into circulation that recruit CXCR4 cells such as hematopoietic stem cells (HSCs) into circulation. However, the direct effect of G-CSF on CXCR4 expression of HSC remains unknown. The nervous system regulates HSC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
1
14
0
1
Order By: Relevance
“…G-CSF has been widely used in the treatment of refractory and relapsed AML together with chemotherapeutic drugs, and has improved the CR rate ( 13 ). Although it is well-established that G-CSF has an important influence on the BMM ( 22 ), there is little research regarding the effect of G-CSF priming chemotherapy on the BMM. G-CSF can promote leukemia cells to be released from the bone marrow into the peripheral circulation by blocking the interaction of SDF-1α and CXCR4, thus enhancing the anti-leukemia effect ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…G-CSF has been widely used in the treatment of refractory and relapsed AML together with chemotherapeutic drugs, and has improved the CR rate ( 13 ). Although it is well-established that G-CSF has an important influence on the BMM ( 22 ), there is little research regarding the effect of G-CSF priming chemotherapy on the BMM. G-CSF can promote leukemia cells to be released from the bone marrow into the peripheral circulation by blocking the interaction of SDF-1α and CXCR4, thus enhancing the anti-leukemia effect ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the SDF-1α/CXCR4 axis using the CXCR4 antagonist, AMD3100, has been indicated to induce leukemia cells to enter the peripheral circulation and induce higher sensitivity to chemotherapeutic drugs ( 21 ). G-CSF, an effective stem cell-mobilizing agent, induces SDF-1α secretion from bone marrow stromal cells into the blood, thus recruiting CXCR4 + cells, including HSCs, into the peripheral circulation ( 22 ). It has been established that G-CSF can promote the expression of transcriptional repressor growth factor independence-1 (Gfi-1), which binds to DNA sequences upstream of the CXCR4 gene and reduces CXCR4 expression in myeloid cells ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…The malignant plasma cells in the niche of multiple myeloma attach to stromal elements using several adhesion receptors. One of the most extensively studied adhesion molecules is CXCR4 and its receptor, stromal cell-derived factor-1 (SDF-1) (Saba et al, 2014[ 31 ]). SDF-1 is produced by osteoblast cells and its receptor, CXCR4, is expressed on myeloma cells.…”
Section: Introductionmentioning
confidence: 99%
“…CXCR4 facilitates homing of MM cells to the BM and leads to adhesion of myeloma cells to the stromal cells, such as osteoblasts and extracellular matrix components; these, in turn, support the growth, survival, and progression of myeloma cells (Alsayed et al, 2007[ 3 ]; Azab et al, 2009[ 8 ]). Studies have shown that CXCR4 is involved in the cross-talk between MM cells and the BM microenvironment (Alsayed et al, 2007[ 3 ]; Azab et al, 2009[ 8 ]; Saba et al, 2014[ 31 ]). Furthermore, VLA-4 integrin plays an important role in the localization of myeloma cells to BM by interacting with its ligands, such as vascular cell adhesion protein-1 (VCAM-1) and connecting segment-1 (CS-1)/fibronectin (Uchiyama et al, 1993[ 36 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Exploiting the beneficial effect of the SDF-1α/CXCR4 axis in cardiac repair has been performed by repeated injections of granulocyte-colony stimulating factor (G-CSF) applied in patients, which aims to release the stem and premature cells from BM and activate the cellular CXCR4 expression of the reparative cells by interrupting the BM-SDF-1α/CXCR4 axis 3 . However, despite the enhanced cell release and migration, and stimulation of the endogenous cardiac progenitor cells, the efficacy of clinical cardiac cell-based therapy in patients with recent acute myocardial infarction (AMI) led to ambiguous results 4 , especially if the regenerative cell therapy was performed very early after ischemic injury 5 .…”
Section: Introductionmentioning
confidence: 99%